Education provision for patients following a spinal cord injury. (28th March 2019) - Rodger, Sian; Bench, Suzanne
Abstract : Background: approximately 40 000 people in the UK live with spinal cord injury. Aim: to explore the views of patients and healthcare staff relating to the specialist education and information provided following a spinal cord injury. Methods: a service evaluation consisting of questionnaire surveys distributed to patients and staff at the London Spinal Cord Injury Centre. Results: of the healthcare staff who responded, 98% found giving education an enjoyable part of their role with most agreeing (45/48) that it is the responsibility of all healthcare staff. The formal education programme was valued by patients. Sessions were graded to inform the development of future programmes. Face to face was the preferred delivery method for 80% of inpatients and 40% of outpatients, with the second most preferred method being an app/e-learning for both patient groups. Conclusion: findings support the continued need for both formal and informal sessions, provided by all members of the healthcare team, with particular emphasis on issues such as bladder and bowel management and sexual function following discharge.